Some interesting problems of Antarctic limnology with special reference to the allelopathic effects on the algal ecology (extended abstract) - Akiyama, Masaru; Hayashi, Masahisa; Ohtani, Shuji; Kanda, Hiroshi (National Institute of Polar Research, 1992)
P(論文) departmental bulletin paper